Biodiversity of Indian Livestock in 13th Century: A Review - Dr Pravin Bankar; Dr Snehal Patil (Journal of Livestock Biodiversity, 2025)
Categorization of domestic animal diversity on the basis of phenotypic traits has been an important step in understanding the life on the earth. Classification of animals on basis of coat color, geographic origin, behavior etc. highlight the earlier attempts for description of phenotypic attributes of domestic livestock. Classification of domestic animals gives idea for understanding history and is essential for an effective conservation of genetic diversity. All modern classification systems have their roots in the Linnaean classification system, developed in the 17th century. However, a systematic attempt for classification of wild and domestic fauna on the basis of behavior and phenotype was done in 13th century only in India. A Jain monk ‘Hansadeva’ have described in detail about classification of domestic and wild animals in his Sanskrit book, ‘Mrigapakshi Shastra’ i.e. Science of animals and birds. This information not only glorifies the ancient Indian knowledge but also provide a valuable base in understanding the animal and birds’ diversity. This article covers the earlier attempt of Indian scholar regarding classification of domestic livestock.